Student-Led Community Service Activities In Indonesia International Institute For Lfe Sciences (I3l) For Building Collaborative Work And Social Awareness - Siti Aisyah FD; Siti Muslimatun; Maria Damayanti G (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
The i3L student-led community service and responsibility (CSR) activities are aimed to foster values of collaborative work and to possess social concerns and responsibility for people and environment. Started in 2014/2015, Student Council and Student Community Clubs managed the CSR activities under the supervision of Centre for Student Development Department. It is compulsory for every student to participate in at least five CSR activities. The CSR activities cover three themes, namely education, environment, and social-economy-culture (SEC). The education theme includes English tutoring program to orphanage children and Science tutoring program for underprivileged primary age children. The Environment theme includes campus waste management program and Clean Up Jakarta. The SEC themes include blood donation, Ramadhan event of charity and iftar, Ribbon Run for mental health awareness, and Animal Shelter visit. In academic year 2018/2019, there were 5, 2, 4 activities conducted under education, environment and SEC themes respectively, involving over 724 participants from students, faculty and educational personnel. The activities were conducted in collaboration with 11 partner institutions. The CSR activities have built collaborative work and social awareness among students and faculties. In future, the impacts of CSR activity for students’ soft-skill competencies and for the society need to be evaluated.